Mortality experience in a polyamide-polyester factory. - Hours, Martine; Bertholon, J.; Esteve, J.; Cardis, Elisabeth; Freyssinet, C. L.; Quelin, P.; Fabry, J. (Scandinavian Journal of Work, Environment & Health, 1986)
Chemical workers have become increasingly concerned about the presence of carcinogens in their occupational environment. As a result, a number of studies of excess cancer mortality have been undertaken in groups of workers with well-characterized exposures. This paper reports the results of one such study carried out in a polyamide-polyester factory in France. A retrospective cohort design was chosen to evaluate the effect of exposure to phthalates, nickel catalyzers, and other chemicals in the work environment. Only a slight excess of cancers, marginally related to exposure category yet not significantly related to length of exposure, was found. The cohort, however, was young but stable, and a continued follow-up is therefore both feasible and justifiable, since it is likely to yield important information about the potential hazards associated with the tergal polymer industry.